SARS-CoV-2 Infection Is at Herd Immunity in the Majority Segment of the Population of Qatar. (2nd May 2021) - Al-Thani, Mohamed H; Farag, Elmoubasher; Bertollini, Roberto; Al Romaihi, Hamad Eid; Abdeen, Sami; Abdelkarim, Ashraf; Daraan, Faisal; Elhaj Ismail, Ahmed Ibrahim Hashim; Mostafa, Nahid; Sahl, Mohamed; Suliman, Jinan; Tayar, Elias; et al.
Abstract: Background: Qatar experienced a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic that disproportionately affected the craft and manual worker (CMW) population, who comprise 60% of the total population. This study aimed to assess ever and/or current infection prevalence in this population. Methods: A cross-sectional population-based survey was conducted during July 26 to September 09, 2020, to assess both anti-SARS-CoV-2 positivity through serological testing and current infection positivity through polymerase chain reaction (PCR) testing. Associations with antibody and PCR positivity were identified through regression analyses. Results: The study included 2641 participants, 69.3% of whom were <40 years of age. Anti-SARS-CoV-2 positivity was 55.3% (95% CI, 53.3%–57.3%) and was significantly associated with nationality, geographic location, educational attainment, occupation, and previous infection diagnosis. PCR positivity was 11.3% (95% CI, 9.9%–12.8%) and was significantly associated with nationality, geographic location, occupation, contact with an infected person, and reporting 2 or more symptoms. Infection positivity (antibody and/or PCR positive) was 60.6% (95% CI, 58.6%–62.5%). The proportion of antibody-positive CMWs who had a prior SARS-CoV-2 diagnosis was 9.3% (95% CI, 7.9%–11.0%). Only seven infections were ever severe, and only 1 was ever critical—an infection severity rate of 0.5% (95% CI, 0.2%–1.0%). Conclusions: Six in every 10 CMWs in Qatar have been infected, suggestive of reaching the herd immunity threshold. Infection severity was low, with only 1 in every 200 infections progressing to be severe or critical. Only 1 in every 10 infections had been previously diagnosed, which is suggestive of mostly asymptomatic or mild infections.